Sending classical information through relativistic quantum channels - Landulfo, André G. S.; Torres, Adriano C. [UNESP] (American Physical Society (APS), 2013)
We investigate how special relativity influences the transmission of classical information through quantum channels by evaluating the Holevo bound when the sender and the receiver are in (relativistic) relative motion. By using the spin degrees of freedom of spin-1/2 fermions to encode the classical information, we show that, for some configurations, the accessible information in the receiver can be increased when the spin detector moves fast enough. This is possible by allowing the momentum wave packet of one of the particles to be sufficiently wide while the momentum wave packets of other particles are kept relatively narrow. In this way, one can take advantage of the fact that boosts entangle the spin and momentum degrees of freedom of spin-1/2 fermions to increase the accessible information in the former. We close the paper with a discussion of how this relativistic quantum channel cannot in general be described by completely positive quantum maps. © 2013 American Physical Society.
Keywords: Accessible information; Classical information; Completely positive; Quantum channel; Relative motion; Special relativity; Spin degrees of freedom; Spin-1/2 fermions; Wave packets; Quantum entanglement